'We Were Refugees and Carried a Special Burden': Emotions, Brazilian Politics and the German Jewish Émigré Circle in São Paulo, 1933–1957. Issue 1 (1st March 2021) - Siegel, Björn
Abstract: By using the example of Jewish immigration to São Paulo in the 1930s and 1940s and analysing the history of the Congregação Israelita Paulista (CIP) under the leadership of Fritz Pinkuss, this article shows how emotions were used in different ways. Such an approach gives new insight into the complexity of migration history. The Brazilian government under Gétulio Vargas openly embraced emotional mobilisation against 'Semites' and 'foreigners', and in so doing wanted to introduce a new understanding of the nation and secure their political influence. At the same time, Pinkuss also used emotions in his communal policies to establish a new religious union, a new form of inclusion and solidarity in the Jewish community. By transferring German Jewish traditions to Brazil and emphasising their flexibility, Pinkuss not only created a new emotional bond, but also laid the ground for integration of the émigré community into Brazilian society.